POED Learning Model to Improve Learning Outcomes and The Tendency to Have Energy Conservation Attitudes in Learners - Nourmayanti, Andrina Eka; Saptono, Sigit; Nugroho, Sunyoto Eko (Lembaran Ilmu Kependidikan, 2022)
Energy conservation is one of the first steps to overcome the scarcity of energy resources in the future, which can be done through educational channels. This study aims to find out the validity, effectiveness, and practicality of using POED (Predict, Observe, Explain and Do) learning model devices used in increasing the tendency to have energy conservation attitudes in learners. In addition, to find out the effectiveness of POED learning model devices to improve learning outcomes in learners. The type of research used is development research that produces products in the form of learning model devices. This research procedure adapts the ADDIE development model consisting of five stages, including: analysis, design, development, implementation and evaluation. Based on the test results of the learning model device, all dimensions included in the criteria are very valid. Learning using POED model devices further increases the tendency to be energy conservation of elementary school learners compared to conventional learning models. The POED learning model is declared practical to use and able to increase the tendency to have energy conservation attitudes in learners. It can be concluded that the use of POED learning model devices is quite effectively used to improve learning outcomes and the tendency to have energy conservation attitudes in elementary school learners.